[2]Pseudorotaxane formation with fret based luminescence response: demonstration ofboolean operations through self sorting on solid surface - Gangopadhyay, Monalisa; Maity, Arunava; Dey, Ananta; Das, Amitava (Journal of Organic Chemistry, 2016)
Binary pseudorotaxane formation between an aza crown derivative as host (H) and two different imidazolium derivatives as guests (G(1) and G(2)) have been studied in detail by NMR (H-1 NMR, 2D NOESY), optical (steady state electronic and emission spectroscopy), and mass spectroscopy. Binding stoichiometry (1:1), association constant for the respective [2]pseudorotaxane formation (K-a(H center dot G1) = (2.61 +/- 0.015) X 10(3) M-1 and K-a(H center dot G2) = (1.27 +/- 0.16) X 10(3) M-1), and associated thermodynamic parameters are also evaluated based on isothermal titration calorimetric (ITC) studies. FRET based luminescence ON responses are observed on formation of the binary pseudorotaxane (H center dot G(1) and H center dot G(2)) in a nonpolar medium like dichlororriethane. The thermodynamic feasibility of such an energy transfer process is also examined. The higher affinity of H and 18-crown-6 toward K+, as compared to those toward G(1) or G(2), and the reversibility in the host- guest binding process are utilized in demonstrating the self-sorting phenomena with associated changes in luminescence responses that could be correlated for Boolean operators like YES, INHIBIT, OR, and AND gates.